2016
DOI: 10.1364/boe.7.004424
|View full text |Cite
|
Sign up to set email alerts
|

Multi-channel multi-distance broadband near-infrared spectroscopy system to measure the spatial response of cellular oxygen metabolism and tissue oxygenation

Abstract: We present a multi-channel, multi-distance broadband near-infrared spectroscopy (NIRS) system with the capability of measuring changes in haemoglobin concentrations (Δ[HbO2], Δ[HHb]), oxidation state of cytochrome-c-oxidase (Δ[oxCCO]) and tissue oxygen saturation (TOI) in the adult human brain. The main components of the instrument are two customized spectrographs and two light sources. Each spectrograph is lens-based to improve light throughput, has a grating enhanced to optimise reflection in the near-infrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 46 publications
(42 reference statements)
1
30
0
Order By: Relevance
“…16,17 Use of the full nearinfrared (NIR) spectrum from 780 to 900 nm obtained by bNIRS has enabled precise measurement of tissue changes in [oxCCO] in animals, neonates, and adults. [18][19][20][21][22][23][24][25][26][27][28][29][30] Cooper et al 31 described the integration of an in-house built bNIRS system with 31 P-MRS to investigate HI in newborn pigs and discussed the physiological/biochemical relationships of these measurements. They reported that the measurement of Δ½oxCCO correlates with changes in energy metabolism measured by 31 P-MRS during HI and early recovery after reperfusion and oxygenation.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Use of the full nearinfrared (NIR) spectrum from 780 to 900 nm obtained by bNIRS has enabled precise measurement of tissue changes in [oxCCO] in animals, neonates, and adults. [18][19][20][21][22][23][24][25][26][27][28][29][30] Cooper et al 31 described the integration of an in-house built bNIRS system with 31 P-MRS to investigate HI in newborn pigs and discussed the physiological/biochemical relationships of these measurements. They reported that the measurement of Δ½oxCCO correlates with changes in energy metabolism measured by 31 P-MRS during HI and early recovery after reperfusion and oxygenation.…”
Section: Introductionmentioning
confidence: 99%
“…fNIRS can monitor the changes in the redox state of CCO using the oxidized minus reduced CCO spectra to obtain a measurement of changes in the concentration of oxidized CCO ([oxCCO]). Thus, this biomarker could be very interesting because it provides another and complementary way to evaluate neural activity [54].…”
Section: Discussionmentioning
confidence: 99%
“…New developments in fNIRS technology will further allow for the monitoring, at least on newborns, of the cytochrome-c-oxidase redox state (CCO), which is also a metabolic marker of oxidative metabolism [111]. The hyperspectral CW NIR technique is currently used by some research groups to monitor in vivo human brain metabolism via measurements of the concentration changes in O 2 Hb, HHb and the oxidation state of CCO to achieve the quantification of cerebral metabolic activation in different situations from functional stimulation to response during oxygen-dependent conditions [23,24]. An increase of the CCO signal, typically corresponding to an increment in cerebral metabolism, was found, for instance, during the functional activation induced by simulated driving [23], the Stroop task [24] or working memory tasks [112].…”
Section: Where Should We Go?mentioning
confidence: 99%
“…The hyperspectral CW NIR technique is currently used by some research groups to monitor in vivo human brain metabolism via measurements of the concentration changes in O 2 Hb, HHb and the oxidation state of CCO to achieve the quantification of cerebral metabolic activation in different situations from functional stimulation to response during oxygen-dependent conditions [23,24]. An increase of the CCO signal, typically corresponding to an increment in cerebral metabolism, was found, for instance, during the functional activation induced by simulated driving [23], the Stroop task [24] or working memory tasks [112]. Unlike the hemodynamic changes that are strongly affected by scalp blood flow changes, the changes in the CCO signal more specifically reflect the brain cortex activation.…”
Section: Where Should We Go?mentioning
confidence: 99%